TAFSIR ESOTERIK AL-MAJLISIY DALAM BIHÃR AL-ANWÃR - Wendri, Novizal (LP2M IAIN Mataram, 2010)
One salient feature of the approach to the Qurâanic exegesis among Shiâi is concerned with the interpretation of the inner meaning (esoteric) of the Qurâan. This study discusses the argument of the esoteric exegesis in the work of Allamah al-Majlisiy, BihÃ¢r al-AnwÃ¢r. He was an influential Muslim scholar in the era of Syah Sulayman and Syah Husayn of the Safawid. The purpose of the work was to disseminate Shiâi doctrine to the people. The work highlights the esoteric interpretation of Imam and therefore it was considered as the continuation of the Imam Jaâfar esoteric tradition. The study demonstrates that one fundamental characters of the esoteric interpretation in the work is its concern on the proportional and balanced element between esoteric and exoteric interpretation. According to al-Majlisiy, the Qurâan contains both inner and outer meanings and dimensions. However, the knowledge about the inner and outer dimensions of the Qurâan exclusively belongs to Imam; none knows such dimensions except Imam. The main focus of al-Majlisiy esoteric interpretation are about leadership (imÃ¢mah) such as the authority of Imam, Imam as the heir and sole interpreter of the Qurâan, the Prophet family circle (ahl bayt) and the obligation to comply Imam. This kind of Shiâi interpretation enriches the tradition of the Qurâanic exegesis in Islam.